Editorial: Unveiling functional and structural physiological transformations through muscle stretching - Cè, E.; Longo, S.; Caldwell, J. (Frontiers in Physiology, 2025)
Muscle stretching is widely recognized as a fundamental component of physicl activity and exercise routines, traditionally applied to improve joint flexibility and increase range of motion (ROM). However, a growing body of evidence suggests that stretching may elicit a broader spectrum of physiological effects beyond musculoskeletal adaptations. Emerging studies demonstrate that stretching can influence neuromuscular performance, cardiovascular function, autonomic nervous system activity, and tissue-level mechanical properties. These effects, which can occur both acutely and chronically, open new perspectives on stretching as a low-intensity yet impactful form of physical intervention suitable for diverse populations, including clinical and aging cohorts.